Understanding EFL students' participation in group peer feedback of L2 writing: A case study from an activity theory perspective. (September 2015) - Yu, Shulin; Lee, Icy
While the last three decades have witnessed a growing body of research on peer feedback in first language (L1) and second language (L2) writing, research about students' motives for participating in group peer feedback has remained underexplored. In order to fill this important gap, this case study, guided by the constructs of activity and motive in activity theory, investigates two Chinese university students' motives for participating in group peer feedback activities in the EFL (English as a foreign language) writing classroom. Multiple sources of data were collected, including video recordings of peer feedback sessions, semi-structured interviews, stimulated recalls and student texts. Data analyses indicate that EFL students' group peer feedback activities are driven and defined by their motives, which are shaped and mediated by the sociocultural context. The findings also show that student motives could have direct influence on students' participation in group peer feedback activities and their subsequent revisions. This study contributes new knowledge to the field by relating students' motives to other key elements in peer feedback such as peer stances, group interaction and student revisions of L2 writing, yielding a deepened understanding of students' participation in and engagement with peer feedback in EFL writing.